Numerical study on the operation rules of hydropower generation - Tan, Benjamin Zhi Wen (2017)
Currently, most cascade dual-reservoir models are incapable of considering the hydraulic links between upstream and downstream reservoirs and of applying different operating rules to each reservoir. Moreover, these models deal directly with complex programming algorithms that make adjustments time-consuming and difficult to comprehend to plant operators and other stakeholders. In this study, a novel object-oriented cascade reservoir model was created using GoldSim to provide a user friendly and neat interface that also accounts for hydraulic linking between reservoirs, based on a feasibility study of a cascade system to be built along the Num Ngum River in Laos. River flows were stochastically generated using gamma distributions and tested for stationarity, before being used in Monte Carlo simulations to investigate the optimality of existing and planned reservoir operating rules. The modeled cascade system was shown to both increase and stabilize the power output of the existing downstream reservoir against seasonal flow variations, and possess good model reliability when inflows are stationary. Simulations using a novel power prediction method proposed herein based on the introduction of discrete drought events were also found to exhibit good accuracy in predicting long-term power output trends under extreme events.